Law’s Silence on Cyberbullying to Children in Indonesia - Putra, Eka Nugraha (Brawijaya Law Journal, 2024)
With the advancement of the Internet, cyberbullying is fast emerging as a significant issue and a new form of violence in Indonesia. Additionally, whether the Internet has become a catalyst for conventional bullying is a critical question that must be addressed. In Indonesia, cyberbullying is now recognized as an imminent concern with regard to juvenile behaviour and development outcomes. The Indonesian legal system, however, has no direct legislation on cyberbullying. The existing laws on juvenile crimes and online offenses do not adequately address specific concerns raised by cyberbullying. This article explores the correlation between high exposure to violent content over the Internet and the recent increase in violence among children in Indonesia. The effect of cyberbullying victimization and its potential to create perpetrators of bullying has been explored within the context of the inadequacy of the current Indonesian legal system’s response to online harassment, particularly the lack of adequate laws against cyberbullying.